Gustavo Gutierrez and the Economic Realities of Africa: An African Theological Reflection - Michael Kwasi IiamofiG Alloteh (E-Journal of Religious and Theological Studies, 2024)
The purpose of this study is to find out how Gustavo Gutierrez used theological reflection and praxis to effectively impact the economic and social life of his home country, Peru and Latin America at large and to establish the lessons African theologians can imbibe from him. The methodology used was a secondary qualitative analysis of literature. In this regard the works of Gutierrez were reviewed. Key strands of African theological reflection were reviewed. The analysis of various perspectives was done to establish their respective impact on the socio-economic life of their people. The key findings are that African theologians were preoccupied with theological phenomenon at seminar and conference levels in coming up with various strands of African theological reflections. On the other hand, Gutierrez did his theological reflection from the point of view of the suffering poor thereby reflecting on what type of theology was needed to permanently change the narratives of the poor. The concluding lessons for African Theologians include a preferential option for the poor, social ministries in the Church should demonstrate incarnation, divine spirituality should entail a commitment to the poor and oppressed, and the establishment of concrete corrective actions. The importance of the Church Community in the divine enterprise for taking ample notice of the presence of the poor and working without fail to change their story. This is a scholarly contribution to harnessing the synergy among strands of African theology towards effective and practical advocacy and activities towards the eradication of abject poverty from Africa and the development of the continent. The paper contributes to the search for practical steps to reduce or end the abject poverty and poor development trajectory in Africa.